2018
DOI: 10.3892/ol.2018.9243
|View full text |Cite
|
Sign up to set email alerts
|

Identifying miRNA‑mRNA regulation network of major depressive disorder in ovarian cancer patients

Abstract: Major depression disorder (MDD) has become increasingly common in patients with ovarian cancer, which complicates the treatment course. The microRNA (miRNA)-mRNA regulation network may help elucidate the potential mechanism of MDD in ovarian cancer. The differentially expressed microRNAs (DEmiRs) and mRNAs (DEmRNAs) were therefore identified from the GSE61741, GSE58105 and GSE9116 ovarian cancer datasets using GEO2R. The target genes of the DEmiRs were then obtained using the TargetScan, microRNAorg, microT-CD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…However, high recurrence rates and high drug resistance rates after relapse are among the most important causes of the high mortality of this disease. Therefore, the metastasis, diagnosis, and treatment of ovarian cancer represent urgent problems that need to be solved [5,6]. To this end, the analysis of the expression of microRNAs (miRNAs), which consist of short-sequence RNAs that do not encode a protein, represents a strategy not only to explore the correlation between miRNA and ovarian cancer but also provide new targets for the diagnosis, treatment, and prognosis of ovarian cancer [5,7].…”
Section: Introductionmentioning
confidence: 99%
“…However, high recurrence rates and high drug resistance rates after relapse are among the most important causes of the high mortality of this disease. Therefore, the metastasis, diagnosis, and treatment of ovarian cancer represent urgent problems that need to be solved [5,6]. To this end, the analysis of the expression of microRNAs (miRNAs), which consist of short-sequence RNAs that do not encode a protein, represents a strategy not only to explore the correlation between miRNA and ovarian cancer but also provide new targets for the diagnosis, treatment, and prognosis of ovarian cancer [5,7].…”
Section: Introductionmentioning
confidence: 99%
“…However, the exact mechanism by which miRNAs promote metastasis in PC has not been fully understood. miR-23b-3p has been shown to promote the development of a variety of different cancers, such as lung cancer, gastric cancer and ovarian cancer, and it was also associated with poor prognosis as well ( 40 43 ). A previous study revealed that miR-23b-3p promotes the proliferation, invasion and migration of PANC-1 cells ( 8 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, hsa-mir-33b can inhibit lung adenocarcinoma cell growth, invasion, and epithelial-mesenchymal transition by suppressing Wnt/ β -catenin/ZEB1 signaling [29]. hsa-mir-33b has also been shown to be dysregulated and prognosis-related in ovarian cancer [30]. However, a report of hsa-mir-33b has not been made for CCA, and the underlying regulatory mechanisms of this important molecule remain largely unclear.…”
Section: Discussionmentioning
confidence: 99%